Case report: uncommon insertion of the extensor pollicis longus muscle: clinical and anthropological significance of this variation. (4th March 2017) - Colak, T.; Bamac, B.; Tekin, Orha A.; Ozbek, A.; Ozturk, O.B.
ABSTRACT: The role of the hand width anthropometric measurement in the estimation of grip strength is seen to be approximately fifty percent. Variation in the extensor pollicis longus muscle is important in daily life based on the fact that the thumb plays an important function, which is to grab objects and to hold them between two fingers. In this study, dissection was being performed on a male cadaver, approximately 55-year-old at the Department of Anatomy, Kocaeli University. Researchers encountered a unilateral extensor pollicis longus muscle va riation that took origin from posterior of the radius and continued at medial side of the extensor pollicis brevis muscle and then ended at the tuberculum radii, whereas the extensor pollicis longus muscle had to end at distal phalange of the thumb. Therefore, information about the anatomic variations of hand and wrist muscles is not for anatomists alone but it is also important for surgeons. For these reasons, it is necessary to follow the variations in the forearm extensor region.